Veterans' Reliance on VA Care by Type of Service and Distance to VA for Nonelderly VA-Medicaid Dual Enrollees. Issue 3 (March 2019) - Yoon, Jean; Vanneman, Megan E.; Dally, Sharon K.; Trivedi, Amal N.; Phibbs, Ciaran S.
Abstract : Background: Not much is known about nonelderly veterans and their reliance on care from the Veterans Affairs (VA) health care system when they have access to non-VA care. Objectives: To estimate VA reliance for nonelderly veterans enrolled in VA and Medicaid. Research Design: Retrospective, longitudinal analysis of Medicaid claims data and VA administrative data to compare patients' utilization of VA and Medicaid services 12 months before and for up to 12 months after Medicaid enrollment began. Subjects: Nonelderly veterans (below 65 y) receiving VA care and newly enrolled in Medicaid, calendar years 2006–2010 (N=19, 890). Measures: VA reliance (proportion of care received in VA) for major categories of outpatient and inpatient care. Results: Patients used VA outpatient care at similar levels after enrolling in Medicaid with the exceptions of emergency department (ED) and obstetrics/gynecology care, which decreased. VA inpatient utilization was similar after Medicaid enrollment for most types of care. VA-adjusted outpatient reliance was highest for mental health care (0.99) and lowest for ED care (0.02). VA-adjusted inpatient reliance was highest for respiratory (0.80) and cancer stays (0.80) and lowest for musculoskeletal stays (0.20). Associations between VA reliance and distance to VA providers varied by type of care. Conclusions: Veterans dually enrolled in Medicaid received most of their outpatient care from the VA except ED, obstetrics/gynecology, and dental care. Patients received most of their inpatient care from Medicaid except mental health, respiratory, and cancer care. Sensitivity to travel distance to VA providers explained some of these differences. Abstract : Supplemental Digital Content is available in the text.